Tamarind fruit extract (Tamarindus indica L.) effectively inhibits the growth of Staphylococcus aureus bacteria: Ekstrak buah asam jawa (Tamarindus indica L.) efektif menghambat pertumbuhan bakteri Staphylococcus aureus - Ni Luh Putu Sri Maryuni Adnyasari; I.G.A Dewi Haryani; Hervina; A.A.Istri Yogi Nareswari Dewi (Makassar Dental Journal PDGI Makassar, 2023)
Periodontal abscess is an infection that is located adjacent to the periodontal pockets and can cause damage to the perodontal li-gament and alveolar bone. One of the gram-positive anaerobic bacteria that play a role in abscess formation is Staphylococcus aureus, and can be inhibited by utilising tamarind fruit (Tamarindus indica L.). This study investigated tamarind fruit pulp ex-tract at concentrations of 10%, 50%, and 100% to inhibit the growth of S.aureus bacteria with true experimental in vitro with post-test only control group design. The treatment group was given 10%, 50%, and 100% tamarind fruit flesh extract. Clinda-mycin as positive control and 96% ethanol as negative control. Bacterial inhibition test on tamarind fruit pulp extract showed strong inhibition response at 10% concentration (13.05±2.21 mm, 50% (28.55±0.78 mm), and 100% (20.21±0.21 mm). It is concluded that tamarind fruit pulp extract can inhibit the growth of S.aureus bacteria.